The Influence of Military Specific Physical Activity on Physical and Cognitive Performance Relevant to Military Operations: Future Directions - Vine, Christopher (Cranfield University, 2020)
Background: The challenging and stochastic nature of military operations require combatants to operate at a high level whilst coping with numerous physical (e.g. load carriage) and cognitive challenges (e.g. decision making). Purpose: To investigate the effect of military specific physical activity (MSPA) on relevant parameters of physical and cognitive performance.Research Design: 1) Developing a representative MSPA protocol and physical and cognitive performance measures. 2) Quantifying the physical demands of the MSPA protocol. 3) Establishing the reliability and validity of the cognitive performance measures. 4) Quantifying the MSPA protocol’s effect on the physical and cognitive performance. Research Progress: A combined load carriage and fire and manoeuvre task was selected as the representative MSPA based on criticality and frequency of completion during military operations. Three physical performance measures well correlated military performance were selected 1) medicine ball throw, 2) weighted counter-movement jump 3) maximal isometric voluntary contraction. To assess cognitive performance a shoot/don’t shoot task and auditory n-back task were chosen based on the importance of working memory during military operations.Military Relevance: The proposed research design should increase the understanding of physical and cognitive function pre-, during-, and post-MSPA and for the development and assessment of mitigation strategies.Background: The challenging and stochastic nature of military operations require combatants to operate at a high level whilst coping with numerous physical (e.g. load carriage) and cognitive challenges (e.g. decision making). Purpose: To investigate the effect of military specific physical activity (MSPA) on relevant parameters of physical and cognitive performance.Research Design: 1) Developing a representative MSPA protocol and physical and cognitive performance measures. 2) Quantifying the physical demands of the MSPA protocol. 3) Establishing the reliability and validity of the cognitive performance measures. 4) Quantifying the MSPA protocol’s effect on the physical and cognitive performance. Research Progress: A combined load carriage and fire and manoeuvre task was selected as the representative MSPA based on criticality and frequency of completion during military operations. Three physical performance measures well correlated military performance were selected 1) medicine ball throw, 2) weighted counter-movement jump 3) maximal isometric voluntary contraction. To assess cognitive performance a shoot/don’t shoot task and auditory n-back task were chosen based on the importance of working memory during military operations.Military Relevance: The proposed research design should increase the understanding of physical and cognitive function pre-, during-, and post-MSPA and for the development and assessment of mitigation strategies.
Keywords: 'Load Carriage'; 'Cognition'; 'Performance'; 'DSDS19'; 'DSDS19 Poster'; 'Cognitive Science not elsewhere classified'; 'Decision Making'; 'Sport and Exercise Psychology'